2012
DOI: 10.1055/s-0032-1315257
|View full text |Cite
|
Sign up to set email alerts
|

The In Vitro Protective Effects of Curcumin and Demethoxycurcumin in Curcuma longa Extract on Advanced Glycation End Products-Induced Mesangial Cell Apoptosis and Oxidative Stress

Abstract: Curcuma longa L. (CLL), a traditional herbal medicine, has been widely used for the prevention of diabetic vascular complications in recent years. However, the protective effects of curcuminoids in CLL on the AGEs-induced damage to mesangial cell are not fully understood. In this present study, dihydroethidium, superoxide dismutase kit, malondialdehyde kit, and acridine orange/ethidium bromide staining methods were used to evaluate the activities of curcumin and demethoxycurcumin (10(-11)-10(-9) M) on AGEs-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 21 publications
1
21
0
Order By: Relevance
“…As shown in l " Fig. 2 Endogenous CAT and GSH-PX deficiency has been regarded as one of the pathogenesis accelerating diabetic renal injury through peroxisomal dysfunction [14,15]. In order to further evaluate the protective effect of Pae and Oxypae on AGEs-induced mesangial cell damage, the activities of CAT and GSH-PX in the supernatant of HBZY-1 mesangial cells were determined by ELISA kits.…”
Section: Abbreviationsmentioning
confidence: 99%
“…As shown in l " Fig. 2 Endogenous CAT and GSH-PX deficiency has been regarded as one of the pathogenesis accelerating diabetic renal injury through peroxisomal dysfunction [14,15]. In order to further evaluate the protective effect of Pae and Oxypae on AGEs-induced mesangial cell damage, the activities of CAT and GSH-PX in the supernatant of HBZY-1 mesangial cells were determined by ELISA kits.…”
Section: Abbreviationsmentioning
confidence: 99%
“…Many of these effects limited the development of DN. Furthermore, treatment of diabetic rats with curcumin prevented diabetesinduced cell apoptosis, oxidative stress and kidney dysfunction [7,8] . However, the mechanisms underlying the renoprotective effects of curcumin in DN remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that AGEs induced apoptosis in renal mesangial cells, vascular endothelial cells and retinal pericytes [22], [23], [24]. Apoptosis in corneal epithelium has been demonstrated in diabetic rat [12], [13], [25], in which the accumulation of AGEs is implicated.…”
Section: Introductionmentioning
confidence: 99%